Financial development, structure and growth: New data, method and results - Kul Bahadur Luintel; Mosahid Khan; Roberto Leon-Gonzalez; Guang Jie Li (Cardiff University, Cardiff Business School, 2016)
The existing weight of evidence suggests that financial structure (the classification of a financial system as bank-based versus market-based) is irrelevant for economic growth. This contradicts the common belief that the institutional structure of a financial system matters. We re-examine this issue using a novel dataset covering 69 countries over 1989-2011 in a Bayesian framework. Our results are conformable to the belief - a market-based system is relevant - with sizable economic effects for the high-income but not for the middle-and-low-income countries. Our findings provide a counterexample to the weight of evidence. We also identify a regime shift in 2008.
Keywords: G0; O4; O16; 330; Financial Structure; Economic Growth; Cointegration; Bayesian Model Averaging; Structural Breaks